Legal Protection Policy for Minority Groups (Evidence from Aboge Group in Purbalingga Indonesia) - Diniyanto, Ayon (JILS (Journal of Indonesian Legal Studies), 2021)
The Aboge Islamic Community in Onje Village is part of a community whose existence must be protected. Without protection, the Aboge Islamic Community in Onje Village has the potential to lose its existence. This study found three hypotheses of problems faced by the Aboge Islamic Community in Onje Village. The three problems include conditional problems, empirical conditions, and sociological conditions. The formulation of the research problem is how to protect the Aboge Islamic Community in Onje Village? and is there a need to protect the Aboge Islamic Community in Onje Village? The research method used in this research is to use a qualitative research approach. This type of research is juridical and sociological. This study succeeded in finding data related to efforts to protect the Aboge Islamic Community in Onje Village. The protection efforts are carried out from within and from outside. Then the researchers also found data related to whether or not a protection policy was needed for the Aboge Islamic Community in Onje Village. The researcher analyzed that the data in the field was found to be necessary and unnecessary. Then the researcher stated that there needs to be a legal policy to protect the existence of the Aboge Islamic Community in Onje Village. The conclusions in this study are to answer two problem formulations